FREQUENCY OF SURGICAL SITE INFECTION AFTER ORTHOPEDICS IMPLANT SURGERY AT NORTHWEST GENERAL HOSPITAL PESHAWAR (Journal of Medical & Health Sciences Review, 2025)
Background:Surgical site infections (SSIs) are a significant complication following orthopedic implant surgeries, often resulting in prolonged hospital stays, increased healthcare costs, and adverse patient outcomes. Despite advances in surgical techniques and infection control, SSIs continue to be a concern, particularly in resource-limited settings. This study aimed to determine the frequency, risk factors, and microbiological profile of SSIs in patients undergoing orthopedic implant surgeries at Northwest General Hospital, Peshawar.Materials and Methods:A prospective descriptive study was conducted from August 2023 to January 2024, involving 78 patients undergoing orthopedic implant surgery. Patients aged 5–75 years were included, while those with previous SSIs, open fractures requiring external fixation, or non-implant surgeries were excluded. Data on demographics, comorbidities, implant types, and postoperative outcomes were collected. SSIs were diagnosed based on clinical signs and confirmed with microbiological culture. Data were analyzed using SPSS version 25; associations were tested using Fisher’s exact and chi-square tests.Results:The mean age was 40 ± 2.13 years; 51.3% were male. The most common procedure was ORIF (44.9%), and plates/screws were the most frequently used implants (39.7%). Only one superficial SSI (1.3%) was observed, with no deep infections. No statistically significant associations were found between SSIs and patient age, gender, implant type, or comorbidities.Conclusion:A low SSI rate (1.3%) was observed, with no deep infections. Rigorous aseptic techniques, early postoperative follow-up, and standardized antibiotic prophylaxis likely contributed to favourable outcomes.